If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4u+3-2(-6u-1)=4(u-1)
We move all terms to the left:
4u+3-2(-6u-1)-(4(u-1))=0
We multiply parentheses
4u+12u-(4(u-1))+2+3=0
We calculate terms in parentheses: -(4(u-1)), so:We add all the numbers together, and all the variables
4(u-1)
We multiply parentheses
4u-4
Back to the equation:
-(4u-4)
16u-(4u-4)+5=0
We get rid of parentheses
16u-4u+4+5=0
We add all the numbers together, and all the variables
12u+9=0
We move all terms containing u to the left, all other terms to the right
12u=-9
u=-9/12
u=-3/4
| -9v-11=-5(v-5) | | 5.6w^2=7w+18 | | 5x+(6−2x)=−(14+2x) | | -7y+5(y+7)=19 | | 11^2x=16 | | 2w+41=91 | | X=y/5+16 | | 6xx=54 | | 22x-5=3(6x-4)+4x+7 | | 15.3+x=22.5 | | F(x)=-x^2-9x+20 | | 8x⁶+215x³-27=0 | | Y=x³+7x-5 | | x-2-x5-x4-23=0 | | 4)4+x)=2(x-8) | | 9=p/3-11 | | 128=x+140 | | 3x−2=46x−4=8 | | -16r+12r=-8 | | Xx+1=1024 | | 2.3x-7=7 | | -x-5x+12=2(12-x) | | 8i+4i-15=9 | | (y=y+16) | | -x-4x+12=2(12-x) | | -3x+10(2x/3)=-11 | | 5(x–6)=4x+4. | | r=4(3.14)(16) | | b/53=3 | | 4x+4=6x–3 | | -3(x+2)=3(x+4) | | -12-14v=-20v |